2005
DOI: 10.1093/bja/aei200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epidural volume extension on dose requirement of intrathecal hyperbaric bupivacaine at Caesarean section

Abstract: This study illustrates that whilst low doses of intrathecal bupivacaine can be effectively used for Caesarean section, at such doses EVE does not appear to offer reliable or clinically relevant reductions in dosing with intrathecal bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 13 publications
1
36
0
3
Order By: Relevance
“…16 As many previous studies supported the dose lowering effect of EVE of our study but Beagle et al who found that EVE has no significant or reliable dose lowering effect on intrathecal dose of bupivaciane. 17 This could be a result of small sample size chosen in this study (30 cases in each group) with only 50% achieving effective dose. 17 It is also possible that the epidural injection of 7 ml was insufficient to cause compartmental compression.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…16 As many previous studies supported the dose lowering effect of EVE of our study but Beagle et al who found that EVE has no significant or reliable dose lowering effect on intrathecal dose of bupivaciane. 17 This could be a result of small sample size chosen in this study (30 cases in each group) with only 50% achieving effective dose. 17 It is also possible that the epidural injection of 7 ml was insufficient to cause compartmental compression.…”
Section: Discussionmentioning
confidence: 91%
“…17 This could be a result of small sample size chosen in this study (30 cases in each group) with only 50% achieving effective dose. 17 It is also possible that the epidural injection of 7 ml was insufficient to cause compartmental compression. They thought this is unlikely as other studies had demonstrated the effect with lower dose of EVE only 5 ml and 6 ml EVE.…”
Section: Discussionmentioning
confidence: 91%
“…Epidural top-ups require www.intechopen.com bupivacaine 0.2-0.5% 10-50 mg with fentanyl 20-25 µg or sufentanil 5-10 µg. Similarly, studies in non-obstetric surgery show that when CSE anesthesia is performed in the sitting position, epidural volume extension does not decrease the dose or raise the level of block produced by subarachnoid hyperbaric bupivacaine (Beale et al, 2005;Rawal, 2005;Tyagi et al, 2008) [A].…”
Section: Pharmacologymentioning
confidence: 99%
“…The spinal component provides rapid onset of anesthesia and the drugs that are administered through the catheter placed in the epidural space maintain analgesia during the postoperative period 1 . The epidural volume extension (EVE) technique is a modifi cation of CSEA in which the level of sensory analgesia obtained via subarachnoid block is increased by a small volume of saline or local anesthetic administered through the epidural catheter [2][3][4][5][6] . The level of sensory block obtained is not only related to the analgesic effect of the local anesthetic administered into the epidural space, but to the effect of the volume of the epidural solution causing cephalic movement of the local anesthetic in the subarachnoid space 5,[7][8][9] .…”
Section: Introductionmentioning
confidence: 99%